2020
DOI: 10.3389/fnins.2019.01433
|View full text |Cite
|
Sign up to set email alerts
|

The Lateral Preoptic Area: A Novel Regulator of Reward Seeking and Neuronal Activity in the Ventral Tegmental Area

Abstract: The lateral preoptic area (LPO) is a hypothalamic region whose function has been largely unexplored. Its direct and indirect projections to the ventral tegmental area (VTA) suggest that the LPO could modulate the activity of the VTA and the reward-related behaviors that the VTA underlies. We examined the role of the LPO on reward taking and seeking using operant self-administration of cocaine or sucrose. Rats were trained to selfadminister cocaine or sucrose and then subjected to extinction, whereby responding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 74 publications
(97 reference statements)
2
19
1
Order By: Relevance
“…VP DREADD expression was mostly localized within strictly-defined VP borders here, though in most rats at least some expression encroached upon nearby subcortical structures containing GABAergic neurons with important behavioral roles (Koob, 2004; Silberman et al, 2009; Jennings et al, 2013; Barker et al, 2017; Saga et al, 2017; Gordon-Fennell et al, 2020), so we cannot definitively exclude overlapping roles for these neurons in behavioral effects.…”
Section: Discussionmentioning
confidence: 80%
“…VP DREADD expression was mostly localized within strictly-defined VP borders here, though in most rats at least some expression encroached upon nearby subcortical structures containing GABAergic neurons with important behavioral roles (Koob, 2004; Silberman et al, 2009; Jennings et al, 2013; Barker et al, 2017; Saga et al, 2017; Gordon-Fennell et al, 2020), so we cannot definitively exclude overlapping roles for these neurons in behavioral effects.…”
Section: Discussionmentioning
confidence: 80%
“…We recently observed that LPO glutamate and GABA neurons play opposing roles in driving motivated behavior, at least in their projections to the lateral habenula, with the activation of GABAergic neurons producing reward and the activation of glutamatergic neurons driving aversion (Barker et al, 2017). Moreover, a recent study observed similar kinds of opposing responses in LPO projections to the ventral tegmental area (Gordon-Fennell et al, 2019). The opposing neuronal subtypes we observed during self-administration may represent a coordinated but opposing response by LPO glutamate and GABA neurons.…”
Section: Discussionmentioning
confidence: 93%
“…Our findings also indicate that only a subset of LPO neurons participate in signaling during cocaine self-administration. It would therefore be of great interest for future studies to examine whether these responsive ensembles comprise a specific cell-type or project to a particular structure; projections to the LHb (Barker et al, 2017), VTA (Gordon-Fennell et al, 2020;Gordon-Fennell et al, 2019), or RMTG (Yetnikoff et al, 2015) are all compelling targets. Additionally, with the recent finding that the LPO may play an important role in drug relapse and decision making during relapse (Gordon-Fennell et al, 2020), more work is needed to determine the roles of specific LPO neuronal subtypes in supporting drug-seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were trained to self‐administer meth in operant chambers equipped with two “nose‐poke” holes, a stimulus light above each hole, an audio tone generator and a house light. Nose‐poking is an ethologically relevant behavior and a commonly employed operant task with rodents (e.g., Brown et al., 2020; Chen et al., 2020; Fredriksson et al., 2019; Gordon‐Fennell et al., 2019; Hong, Kang, Chen, & Choi, 2019; Oliva & Wanat, 2019). Each operant chamber was enclosed in a ventilated, sound‐attenuating chamber.…”
Section: Methodsmentioning
confidence: 99%